2020
DOI: 10.1186/s12905-020-00963-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of BMI on blood value of patients on HCG day with IUI treatment

Abstract: Background This study aims to analyze the effect of the body mass index (BMI) on E2, P and LH values in females who received intrauterine insemination (IUI) treatment on human chorionic gonadotropin (HCG) day. Methods A total of 2319 cycles of IUI-assisted pregnancy treatment were selected in our hospital. Based on the BMI, female infertility patients are divided into three groups: normal weight group, overweight and obese group. Results For patients with natural cycles and ≤ 35 years old, there were 440, 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 27 publications
4
7
0
Order By: Relevance
“…Similarly, only one study with a subgroup of women aged < 35 years, reported lower levels of serum LH in obese women compared to women of normal weight, whereas no difference was observed in women aged > 35 years. This was similar to the findings of three other studies [42,43,48,52]. Finally, in one study, BMI correlated negatively with serum LH levels [43].…”
Section: Gonadotropinssupporting
confidence: 90%
See 3 more Smart Citations
“…Similarly, only one study with a subgroup of women aged < 35 years, reported lower levels of serum LH in obese women compared to women of normal weight, whereas no difference was observed in women aged > 35 years. This was similar to the findings of three other studies [42,43,48,52]. Finally, in one study, BMI correlated negatively with serum LH levels [43].…”
Section: Gonadotropinssupporting
confidence: 90%
“…This was similar to the findings of three other studies [42,43,48,52]. Finally, in one study, BMI correlated negatively with serum LH levels [43].…”
Section: Gonadotropinssupporting
confidence: 90%
See 2 more Smart Citations
“…BMI may affect the IUI outcomes in several aspects. While BMI is negatively associated with hormone levels and follicular growth 16 , Souter et al suggested that BMI was positively associated with endometrial thickness, suggesting that higher BMI may be a favorable factor for endometrial receptivity as soon as "the medication and response are adjusted to overcome the weight effect" 14 . Therefore, heterogeneity in medication and the patients' response may contribute to the difference in the effect of BMI shown by previous studies.…”
Section: Discussionmentioning
confidence: 99%